Selenium Serum Concentration in Awassy Male Lambs: Saadi AG AL-Sammarraie MH AL-Judi Wasan AG AL–Dulimy. - AL-Sammarraie, Saadi AG . (The Iraqi Journal of Veterinary Medicine, 2011)
Selenium interacts with a number of other common dietary constituents primarily at the pharmacokinetic level (uptake distribution and elimination ). These interactions modulate both the nutritional and toxic properties of selenium ( 1,2,3and4). The serum concentration of selenium in five normal healthy Awassy male lambs aged 4- 6 months and their weight ranged between 16 -26 Kg and kept in a semi closed system in Baghdad area (Iraq) was measured by using flameless atomic absorption (ShematzoJapan) (2) using a selenium standard ( Wunstor for Stabe 40 D -3016 Seeize 1 / Hannover ). Every two weeks and for twenty weeks 5 ml. blood samples were collected from the jugular vein of the lambs in a sterile test tubes without anticoagulant to obtain serum (5). The results showed that the means of selenium serum concentration ranged between 0.48 to 0.51μmol /L. These results were in agreement with (6,7and8).The reduction of selenium by rumen is heavily influenced by other dietary factors and ruminants exhibits greater variation in selenium absorption than monogastric animals (9and10).